Sistem Pemantau dan Pengontrol Suhu dan pH Air Otomatis pada Budidaya Ikan Gabus - Meutia, Ernita Dewi; Utama, Muhammad Yoga; Munadi, Rizal; Irhamsyah, Muhammad (Yayasan Kawanad, 2023)
Maintaining the temperature and pH of water in fish farming is important to maintain the survival of the commodities being cultivated. Snakehead fish as one of the freshwater fish cultivation commodities, live in a temperature range of 25° to 32°C, and a pH of 4,5 to 6. Changes in temperature and pH due to differences in day and night and weather conditions can be mortal for the fish. To help the fish farmers maintain water quality, in this research a prototype of IoT based temperature and pH monitor and control was built using Arduino microcontroller, that can be accessed through a mobile application on Android smartphone. The test results show that the prototype has successfully control the temperature by turning the heater on when it dropped below 25°C, turned the acid solution pump on when the pH felt below 4.5, and alkaline solution pump when pH was above 6. Continuous sensor readings are able to maintain the stability of water quality.